2020
DOI: 10.3390/polym13010064
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Pectic Polysaccharide Isolated from Diospyros kaki Leaves on Tumor Cell Angiogenesis via VEGF and MMP-9 Regulation

Abstract: Persimmon leaves are an attractive source of phytochemicals with potential health benefits. However, there are only a few reports on the chemical properties and biological activity of the polysaccharide fractions (PLE-I–III) of persimmon leaves. We evaluated the angiogenesis-inhibiting ability of pectic-polysaccharides. The molecular weight of PLEs was determined using a high-performance size-exclusion chromatography system. Tube formation assay of human umbilical vein endothelial cells (HUVECs) was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Vascular endothelial growth factor is a homodimeric growth factor that is structurally expressed in the brain. It is up-regulated during hypoxia and ischemia and is part of the adaptive response to protect tissue from injury [ 31 ]. In-vivo studies have shown that, after stroke, when VEGF is locally supplied by the lateral ventricle, it reduces the infarct scope, improves neurological deficits, and prevents delayed neuronal injury by inhibiting caspase-3 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor is a homodimeric growth factor that is structurally expressed in the brain. It is up-regulated during hypoxia and ischemia and is part of the adaptive response to protect tissue from injury [ 31 ]. In-vivo studies have shown that, after stroke, when VEGF is locally supplied by the lateral ventricle, it reduces the infarct scope, improves neurological deficits, and prevents delayed neuronal injury by inhibiting caspase-3 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The total protein amount was measured using a bicinchoninic acid assay, and the concentration of each sample was adjusted accordingly. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis, protein transfer, and the membrane development were performed as described in previous reports [ 32 , 33 ]. The protein concentration was determined using the Pierce™ BCA Protein Assay Kit (Pierce, Rockford, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Polysaccharides of PL are mainly a group of hetero-polysaccharides, and the most common polysaccharides units are glucose, galactose, arabinose, mannose, and rhamnose. For example, Park et al [ 51 ] suggested that polysaccharide fraction I of PL is mainly composed of galactose (29.9%), galacturonic acid (16.7%), arabinose (17.8%), rhamnose (10.4%), and trace amounts of 3-deoxy-D-manno-2-octulosonic acid (KDO)-like materials (0.9%). Fraction II was composed of 27.2% acidic sugars (glucuronic acid and galacturnonic acid), 19.6% arabinose, 19.4% rhamnose, 13.6% galactose, and 9.6% KDO-like compounds, including 2-methyxylose (3.3%), 2-methylfucose (3.0%), and KDO (3.1%).…”
Section: Bioactive Compounds Of Plmentioning
confidence: 99%